Exploring the Mediating Effect of Job Satisfaction on the Compensation Performance Relationship in a Fast-Moving Consumer Goods Company - Dhyah Harjanti; Fadel Brilliant Sugito; Wilma Laura Sahetapy (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2025)
This study highlights the importance of human resources in maintaining company performance and sustainability. In the context of a Fast-Moving Consumer Goods Company, compensation is viewed as a strategic factor that can improve employee motivation and work results. Job satisfaction is considered a potential link between compensation and employee performance. This study used a quantitative approach with 150 respondents who had worked for at least one year. Data were analyzed using SmartPLS 4.0. The results showed that compensation had a positive and significant effect on job satisfaction, and job satisfaction had a positive effect on employee performance. In addition, compensation was proven to have a significant direct effect on employee performance and also had an indirect effect through job satisfaction as a mediating variable.